Bilateral Peritonsillar Abscess: a case report - Dongol, K (Journal of Institute of Medicine Nepal, 2016)
Although unilateral peritonsillar abscess is a common problem in otorhinolaryngology, case of bilateral peritonsillar abscess is very rare. Not a single case of bilateral peritonsillar abscess has been reported from Nepal till date. This is a case report of a 52 years old lady who presented with bilateral peritonsillar abscess in emergency and was managed with incision and drainage and antibiotics.